Operational background air pollution prediction over Slovenia by QualeAria modelling system – validation. (1st January 2014) - Božnar, Marija Zlata; Mlakar, Primož; Grašič, Boštjan; Calori, Giuseppe; D'Allura, Alessio; Finardi, Sandro
Slovenia is a country of very complex terrain and many problems with air pollution in the valleys, canyons and basins, where industrial air pollution is combined with traffic and domestic heating air pollution, giving rise to problems for the health impact and the ecosystems directly or indirectly. Among indirect effects is also effect on solar radiation budget because of photochemical smog and especially particulate air pollution. To assess air pollutants over the country, a preliminary application of an experimental operational forecast system is presented here, with the aim of exploring its potentials and limitations in modelling the background air quality, and to focus the aspects where improvements are needed for a true operational use.